Measuring the Level of Readiness for Integrated Business Startup System Adoption for SMEs Using the E-Readiness Model Approach - ., Febrianty; Hadiwijaya, Hendra; Barovih, Guntoro; ., Adelin (KnE Social Sciences, 2023)
The study aims to analyze the level of readiness for the adoption of the IBS (Integrated Business Startup) system for SMEs in the city of Palembang. The method used is the e-readiness method using 6 indicators, namely: Awareness, government, commitment, business resources, human resources, technology resources, and adoption. The method of determining respondents is by using the census method. The respondents are SMEs in South Sumatra Province, which is under the guidance of the Department of Cooperatives and SMEs of South Sumatra Province, and which has been registered as IBS users as many as 280 SME respondents. The measurement results show that SMEs in Palembang City have a level of readiness to use information technology facilities to market their products through the IBS system. Based on the measurement results on the indicators used, the results show that the awareness indicator has a value of 3.50, the governance indicator has a value of 2.98, commitment has a value of 2.95, business resources has a value of 3.90, human resources have a value of 2.64, technological resources have a value of 2.96 while adoption has a value of 3.20. The value obtained shows that the level is quite ready to adopt the IBS system. Keywords: IBS, e-Readiness, adoption, SMEs, Department of Cooperatives and SMEs of South Sumatra Province